Edukasi interaktif pencegahan stunting dan kesehatan gigi anak prasekolah melalui pemberian PMT Moris Cookies berbahan daun kelor - Dientyah Nur Anggina; Resy Asmalia; Tarishah Jannah Fatihah; Daniswara Lucretia; Naura Hisanah Ganeshty; Nur Hartini; Rafifah Shabirah; Erlangga Yoga Pratama; Meita Liani Putry; M. Kevin Astradarmawan (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Stunting is a long-term nutritional issue that impacts children’s physical and cognitive development. Efforts to prevent stunting need to be initiated early through nutritional education and improvement of health behaviors, including oral hygiene. Nutritional problem and dental health are interrelated because dental and oral disorders such as caries can reduce children’s appetite and nutritional intake, thereby worsening the risk of stunting. This activity aimed to increase the nutritional knowledge and understanding the oral hygiene of preschoolers and parents through interactive education and supplementary feeding (PMT) of Moris Cookies made from Moringa Leaves as a source of nutrients. This activity was conducted at PAUD Mutiara Hati, Jejawi Village, involving 20 children and parents. The education was delivered through stunting counceling, the practice of brushing teeth using Tooth Doll and the distribution of PMT Moris Cookies. The result of this activity showed that 66.6% of respondents understood the educationional materials provided, and the children showed enthusiasm for the consumption of Moris Cookies and the practice of brushing their teeth. This activity contributed to improving nutrition and oral hygiene knowledge and it is expected to be the first step in supporting stunting prevention efforts at the preschoolers level.